Geochemical features of Kulunda plain lakes (Altay region, Russia); IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Kolpakova M. N. Marina Nikolaevna; Shvartsev S. L. Stepan Lvovich; Borzenko S. V.; Isupov V. P.; Shatskaya S. S. (Hydrogeochemistry, 2016)
Title screen